The Effectiveness of Using Jengkol Peel Extract (Pithecellobium lobatum Benth.) in Inhibits Bacterial Growth Staphylococcus aureus In Vitro - Indra Basar Siregar; Gostry Aldica Dohude; Rahmi Syaflida Dalimunte; Zata Amani, A Rachma (HM Publisher, 2023)
Staphylococcus aureus is aerobic bacteria that are gram-positive and are one of the normal human flora on the skin and mucous membranes. Most infections in the oral cavity are caused by Staphylococcus aureus, which is a normal flora in the oral cavity that can turn into a pathogen if trauma or abrasion occurs on the mucosal surface. Jengkol peel is thought to contain tannin compounds, which have the potential as an anti-inflammatory, anti-diarrheal, antioxidant, treatment of infections of the skin and mouth, and treatment of burns. This study aimed to explore the potential of jengkol peel extract (Pithecellobium lobatum Benth.) as an antibacterial Staphylococcus aureus regularly in vitro. This study is an experimental research in vitro, where as many as 7 treatment groups were used in this study. Positive and negative controls and extract concentrations of 5%-80% were used as the treatment group. Analysis of the average diameter of the inhibition of bacterial growth was carried out using SPSS version 25 software. The potential inhibition of jengkol peel extract was in line with the increase in the concentration of jengkol peel extract. The higher the concentration of jengkol peel extract, the greater the inhibition of bacterial growth. Extract concentration of 20% has a comparable inhibition of bacterial growth control positive. Jengkol peel extract effectively inhibits the growth of Staphylococcus aureus bacteria. Jengkol peel extract concentration of 20% has effectiveness in inhibiting bacterial growth equivalent to 0.2% chlorhexidine in vitro.